On functions between generalized topological spaces - Bayhan, Sadik; Kanibir, A.; Reilly, Ivan L. (Applied general topology, 2013)
This paper investigates generalized topological spaces and functions between such spaces from the perspective of change of generalized topology. In particular, it considers the preservation of generalized connectedness properties by various classes of functions between generalized topological spaces.